Effect of artificial insemination practices on the improvement of income of dairy cattle farmers in West Java - Sugiarti, Tatit; Siregar, Sori B (Indonesian Journal of Animal and Veterinary Sciences, 1999)
A study was done to evaluate the effect of artificial insemination (AI) on the improvement of farmers income. This study was conducted in Bandung district, where doing cattle population was concentrated, from which four locations were chosen, namely : Pangalengan, Kertasari, Lembang and Cisarua. In this study 1,800 non pregnant and healthy cows were selected. Artificial Insemination practices applied were : insemination at 60-90 days post partum precise check estrous and precise insemination time (9-24 hour after the first sign of estrous). Data of these 1,800 cows collected in the previous study was used as control data. Pregnancy was determined through non return rate (NRR) method and confirmed by rectal palpation. To study the impact of AI on farmers income, 30 farmers from each location were sampled. Data was obtained through a survey and was analysed based on descriptive and partial methods as it is commonly used in similar studies. The dairy cattle farming in each location was only part of the agriculture business own by farmers. Therefore the composition of cattle raised was not balanced productive and nonproductive cattle. Practices of AI in this study significantly reduce the lactation length : 363 to 312 days for Pangalengan, 355 to 316 days for Kertasari, 368 to 313 days for Lembang and 348 to 321 days for Cisarua. This optimalization of lactation length increases the farmers income as much as follow : Rp 615.02/head/days for Pangalengan, Rp 615.17 /head/day for Kertasari, Rp 601.32/head/day for Lembang and Rp 301.08/head/day for Cisarua. The application of AI practices in this study affect the income of farmers significantly, but the real application in rural areas needs special attention especially on the facilities for AI, in order to get the optimum result. Â  Key words : Dairy cows, AI, lactation length, milk production, farmers income Â